Development of an AI solution for surgical gauze management - Ang, Soon Kim (Nanyang Technological University, 2021)
Gossypiboma/textiloma is an avoidable medical complication caused by human error. It has been inferred to be under reported due to the medicolegal nature of the situation with cases reported only for insurance claim. The surfacing of such cases causes unnecessary damage to the patient well-being as well as the surgeon and hospital reputation. Several solutions ranging from manually counting of the gauze to the physical tracking of the gauze using Radio Frequency Identification (RFID) tags has been implemented with varying success with each method having their own benefit and costs. This project aims to tackle the problem using the ever-evolving field of Artificial Intelligent (AI) which can be cheaper to implement compared to the current RFID solution as well as being less labor intensive compared to manual counting. A prototype system will be conceptualized and constructed by implementing the solution into common devices such as smart phone which could be easily deployed to various location. By assisting in the accounting of the gauze, human error can be minimized, and the prototype can be easily scaled up and distributed for practical usage to other organization that requires such a solution.